Clinical Characteristics of Patients with Isolated Calf Vein Thrombosis in a Large Teaching Hospital - Santin Brian; B. Fries Richard; Satiani Bhagwan (International Journal of Vascular Medicine)
Objective. To identify the clinical characteristics of a patient population newly diagnosed with acute isolated calf deep venous thrombosis (ICDVT) by duplex ultrasound scan (DUS). Methods. A retrospective review of the records of 100 consecutive patients diagnosed with ICDVT by DUS was conducted. Results. Patients (59% male) were predominantly Caucasian (86%) and inpatients (69%) with an average age of 53 years. The most frequent risk factors were malignancy (22%), immobility (18%), and previous DVT (13%). Thrombus was present in named tibial veins in 58% and muscular branches in 42%. The peroneal vein was most frequently involved (39/117, 33%) followed by the gastrocnemius veins (29/117, 22%) and muscular calf tributaries (14%). Conclusions. Our patient population with ICDVT was predominantly symptomatic, in-patient cohort with a high incidence of risk factors such as malignancy, immobility, previous DVT, trauma, and postoperative status. Partial or complete resolution was documented by DUS in 53%.